2021
DOI: 10.1186/s13550-021-00805-7
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic safety of 177Lu-PSMA-617 radioligand therapy in patients with metastatic castration-resistant prostate cancer

Abstract: Background Myelosuppression is a potential dose-limiting factor in radioligand therapy (RLT). This study aims to investigate occurrence, severity and reversibility of hematotoxic adverse events in patients undergoing RLT with 177Lu-PSMA-617 for metastatic castration-resistant prostate cancer (mCRPC). The contribution of pretreatment risk factors and cumulative treatment activity is taken into account specifically. Methods RLT was performed in 140 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Three patients developed visceral metastases under 223 Ra (one patient with adrenal, one with pulmonary and one with splenic metastases, respectively). Upon initiation of 177 Lu-PSMA-617, 16 patients had low (oligo-/multifocal; ≤20 lesions) and 12 patients had high (disseminiated/diffuse; >20 lesions) bone tumor burden (based on PROMISE miTNM and previous studies) [17][18][19].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Three patients developed visceral metastases under 223 Ra (one patient with adrenal, one with pulmonary and one with splenic metastases, respectively). Upon initiation of 177 Lu-PSMA-617, 16 patients had low (oligo-/multifocal; ≤20 lesions) and 12 patients had high (disseminiated/diffuse; >20 lesions) bone tumor burden (based on PROMISE miTNM and previous studies) [17][18][19].…”
Section: Resultsmentioning
confidence: 91%
“…In the VISION study, 68/529 (12.9%) patients developed grade ≥ 3 anemia, 42 (7.9%) thrombocytopenia and 13 (2.5%) leukopenia [9]. In a recent study by Groener et al, significant hematologic adverse events were observed in a total of 13/140 patients (9.3%) after 177 Lu-PSMA-617 [19]. Here, previous treatment with 223 Ra was not significantly associated with occurrence of hematotoxicity (OR: 0.93, 95% CI 0.27-3.20, p = 0.58).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At median follow-up of 8 months, no cases of late-onset severe myelosuppression or myelodysplastic syndrome were reported. 25 Another study showed hematological safety of [ 177 Lu]Lu-PSMA-617 in patients with high bone tumor burden. 22 …”
Section: The Real Worldmentioning
confidence: 99%
“…Hematologic adverse events have been reported more frequently than diminished renal function with 177 Lu-PSMA-617. For example, Rahbar et al reported grade 3-4 hematotoxicity in 12% of patients (3% leukopenia, 10% anemia, and 4% thrombocytopenia) in a multicenter trial, and Groener et al reported similar numbers (9.3%; 3.6% leukopenia, 7.1% anemia, and 4.3% thrombocytopenia) [9,10]. There are several risk factors for hematotoxicity, e.g., patients with high occurrence of bone metastases, previous chemotherapy with taxane, or pretreatment grade 2 cytopenia [10].…”
Section: Introductionmentioning
confidence: 99%